Northwestern overthrusting and related lateral escape during the Brasiliano orogeny north of the Patos lineament, Borborema province, northeast Brazil - Hackspacher, Peter Christian [UNESP]; Dantas, Elton Luiz [UNESP]; Brito Neves, Benjamin Bley; Legrand, Jean Michel (Taylor & Francis, 1997)
The Borborema province (BP) of northeastern Brazil, located between the São Luís and São Francisco cratons, represents a branching system of Precambrian orogens of the South American platform. It is composed of segments of Archean and Proterozoic crust that were deformed by the convergence of the West African and São Francisco-Congo cratons during assembly of the Brasiliano collage (650 to 500 Ma), a period of intense orogenic activity considered to be the strongest and most pervasive tectonic event that affected the Precambrian of the South American platform. The tectonic and kinematic history of the Brasiliano/Panafrican orogeny is fundamental for reconstructing South American and African Precambrian geology. The correlation between Neoproterozoic tectonic processes occurring in both continents should use structural elements, of regional or local character, with identical kinematic and metamorphic conditions manifested in both basement and supracrustal units. North of the Patos shear zone, subhorizontal Brasiliano thrusts (0.65 to 0.58 Ga) affected the basement and the supracrustal Seridó belt with such related regional D1/D2 structures as foliation, lineation, isoclinal folds, and related metamorphism. Overprinting the previous structures, regional folding with a vertical S3 foliation and an associated strike-slip shear zone were developed (0.58 to 0.52 Ga). The metamorphism is similar for all deformation phases, ranging from upper-greenschist to amphibolite facies with mineral assemblages including biolite and garnet throughout the Seridó fold belt. We propose, on the basis of deformational and kinematic reconstructions, that the structural evolution of the Seridó fold belt was characterized by transition from a syn-collisional to a strike-slip regime. The transition between regimes occurred, progressively or instantaneously, by the switching of the maximum and intermediary strain axes of the strain ellipsoid. The entire tectonic history can be related to a frontal or oblique collision and lateral escape tectonics, with local, syn-collisional transpression and transtension. The Patos shear zone represents a final vertical shearing, juxtaposing different terranes of the northern and southern Borborema province.